Activity coefficients of dipotassium phthalate and potassium hydrogen phthalate in water at 298.15K - Mendonça, António (2022)
Pitzer model parameters and modified Guggenheim equation parameters for dipotassium phthalate (K2PH) and potassium hydrogen phthalate (KHPh) were determined from cell potential difference (cpd) measurements on galvanic cells without liquid junction. Mean activity coefficients of these salts in water at 298.15 K were calculated by the Pitzer model and modified Guggenheim equations. The Pitzer parameters values obtained for K2Ph where: Beta 0(K2Ph)+steta(Cl,Ph) = 0.25 ± 0.01 mol−1 kg; Beta 1 (K2Ph)= 0.86 ± 0.08 mol−1 kg; C(K2Ph)= −0.010 ± 0.002 mol−2 kg2 and ΨK,Cl,Ph = 0.014 ± 0.005 mol−2 kg2. The Pitzer parameters values obtained for KHPh were: Beta0 (KHPh + steta(Cl,Ph)= 0.084 ± 0.013 mol−1 kg, = 0 mol−1 kg. The results were also compared to the values obtained from Pitzer parameters published in literature. The parameter values for the modified Guggenheim equations (bK,Ph = −0.041 mol−1 kg and bK,HPh = −0.020 mol−1 kg) obtained in this study were used in the mean activity coefficients calculations. The modified Guggenheim equation allows us to obtain similar mean activity coefficient values, as the Pitzer equation, up to 1.5 mol kg−1 ionic strength for K2Ph and 0.5 mol kg−1 for KHPh.